Simulations of the Present and Late-Twenty-First-Century Western North Pacific Tropical Cyclone Activity Using a Regional Model - Wu, Liang; Chou, Chia; Chen, Cheng-Ta; Huang, Ronghui; Knutson, Thomas R.; Sirutis, Joseph J.; Garner, Stephen T.; Kerr, Christopher; Lee, Chia-Jung; Feng, Ya-Chien (Journal of climate, 2014)
A high-resolution regional atmospheric model is used to simulate present-day western North Pacific (WNP) tropical cyclone (TC) activity and to investigate the projected changes for the late twenty-first century. Compared to observations, the model can realistically simulate many basic features of the WNP TC activity climatology, such as the TC genesis location, track, and lifetime. A number of spatial and temporal features of observed TC interannual variability are captured, although observed variations in basinwide TC number are not. A relatively well-simulated feature is the contrast of years when the Asian summer monsoon trough extends eastward (retreats westward), more (fewer) TCs form within the southeastern quadrant of the WNP, and the corresponding TC activity is above (below) normal over most parts of the WNP east of 125°E. Future projections with the Coupled Model Intercomparison Project phase 3 (CMIP3) A1B scenario show a weak tendency for decreases in the number of WNP TCs, and for increases in the more intense TCs; these simulated changes are significant at the 80% level. The present-day simulation of intensity is limited to storms of intensity less than about 55 m s−1. There is also a weak (80% significance level) tendency for projected WNP TC activity to shift poleward under global warming. A regional-scale feature is a projected increase of the TC activity north of Taiwan, which would imply an increase in TCs making landfall in north China, the Korean Peninsula, and parts of Japan. However, given the weak statistical significance found for the simulated changes, an assessment of the robustness of such regional-scale projections will require further study.